Pablo no fue cristiano : el mensaje original de un apóstol mal entendido - Eisenbaum, Pamela Michelle; Pérez Escobar, José (Estella (Navarra), España : Editorial Verbo Divino, 2014)
Reveals the historical Paul, not as the founder of a new Christian religion, but as a devout Jew who believed Jesus was the Christ who would unite Jews and Gentiles and fulfill God's universal plan for humanity.
Includes bibliographical references.
Online resource; title from ePub cover page (Digitalia, viewed July 15, 2016)
Keywords: Paul, -- the Apostle, Saint; Electronic books